101k views
1 vote
What’s the inverse function

What’s the inverse function-example-1

2 Answers

3 votes

Answer:


\laege\boxed{f^(-1)(x)=-2x+6}

Explanation:


f(x)=3-(1)/(2)x\to y=3-(1)/(2)x\\\\\text{Exchange x to y and vice versa:}\\\\x=3-(1)/(2)y\\\\\text{Solve for}\ y:\\\\3-(1)/(2)y=x\qquad\text{subtract 3 from both sides}\\\\-(1)/(2)y=x-3\qquad\text{multiply both sides by (-2)}\\\\\left(-2\!\!\!\!\diagup^1\right)\cdot\left(-(1)/(2\!\!\!\!\diagup_1)y\right)=-2x-3(-2)\\\\y=-2x+6

User Wnbell
by
6.1k points
4 votes

Answer:


f^(-1)(x)=-2x+6.

Explanation:


y=f(x)


y=3-(1)/(2)x

The biggest thing about finding the inverse is swapping x and y. The inverse comes from switching all the points on the graph of the original. So a point (x,y) on the original becomes (y,x) on the original's inverse.

Sway x and y in:


y=3-(1)/(2)x


x=3-(1)/(2)y

Now we want to remake y the subject (that is solve for y):

Subtract 3 on both sides:


x-3=-(1)/(2)y

Multiply both sides by -2:


-2(x-3)=y

We could leave as this or we could distribute:


-2x+6=y

The inverse equations is
y=-2x+6.

Now some people rename this
f^(-1) or just call it another name like
g.


f^(-1)(x)=-2x+6.

Let's verify this is the inverse.

If they are inverses then you will have that:


f(f^(-1)(x))=x \text{ and } f^(-1)(f(x))=x

Let's try the first:


f(f^(-1)(x))


f(-2x+6) (Replace inverse f with -2x+6 since we had
f^(-1))(x)=-2x+6


3-(1)/(2)(-2x+6) (Replace old output, x, in f with new input, -2x+6)


3+x-3 (I distributed)


x

Bingo!

Let's try the other way.


f^(-1)(f(x))


f^(-1)(3-(1)/(2)x) (Replace f(x) with 3-(1/2)x since
f(x)=3-(1)/(2)x)


-2(3-(1)/(2)x)+6 (Replace old input, x, in -2x+6 with 3-(1/2)x since
f(x)=3-(1)/(2)x)


-6+x+6 (I distributed)


x

So both ways we got x.

We have confirmed what we found is the inverse of the original function.

User Hammygoonan
by
5.9k points